PENGARUH HARGA, LOKASI DAN DIGITAL MARKETING TERHADAP LOYALITAS PELANGGAN DENGAN KEPUASAN PELANGGAN SEBAGAI VARIABEL INTERVENING - Simanihuruk, Peran; Tamba, Darwis; Purba, Antonius M; Sitorus, Putri Dwi Ana (KUKIMA : Kumpulan Karya Ilmiah Manajemen, 2024)
The objective of this research is to analyze the influence of price, location, and digital marketing on customer loyalty, with customer satisfaction as an intervening variable. The research population includes all visitors who have used the services of Atsari Hotel Parapat, while the research sample consists of 99 respondents. Data collection techniques employed were questionnaires and documentation, and data analysis was conducted using SMART PLS-4. The research results indicate that price does not have a positive and significant effect on customer satisfaction when examined partially. Similarly, price does not have a positive and significant effect on customer loyalty when examined partially. Location has a positive and significant effect on customer satisfaction when examined partially. Location also has a positive and significant effect on customer loyalty when examined partially. Digital marketing has a positive and significant effect on customer satisfaction when examined partially. Digital marketing also has a positive and significant effect on customer loyalty when examined partially. Customer satisfaction, when examined partially, has a positive effect on customer loyalty. Price does not have a positive and significant effect on customer loyalty with customer satisfaction as an intervening variable. Location does not have a positive and significant effect on customer loyalty with customer satisfaction as an intervening variable. Digital marketing has a positive and significant effect on customer loyalty with customer satisfaction as an intervening variable. With an R-Square value, customer loyalty can be explained by 72.2%, while the remaining 27.8% is influenced by other factors. Customer satisfaction can be explained by 42.6%, while the remaining 57.4% is influenced by unknown factors not covered in this research.